Instructional animation design: the influence of render styles at the cognitive stage of psychomotor learning / Terry Lukas @ Lucas - Lukas @ Lucas, Terry (2018)
There have been several studies investigating the effectiveness of two-dimensional visual representation and three-dimensional visual representation. Areas that are similar to this study are in information visualisation, simulation, user interface and virtual navigation. However, the findings from these studies are relatively inconsistent. The research specifically focused on psychomotor learning as this area of study is still relatively under-researched. Moreover, recent studies show that animation is effective in learning procedural tasks. Nevertheless, based on the recommendations of these studies, more research is needed to narrow the gap on the underlying visual characteristics of the digital human representations and its techniques. Hence, this research aims to investigate the effectiveness and the efficiency of various virtual human representations such as two-dimensional visual and three-dimensional visual in motor skills acquisition. The first phase is to investigate the underlying characteristics and applications of animated digital human representations in instructional animations. Explorative studies via a hybrid of directed and interpretive content analysis grounded on Cognitive Theory of Multimedia Learning on the specific design features and visual representations were analysed. This study found common characteristics and unique approaches to creating instructional animation. The second phase is to propose a theoretically based instructional animation design framework for psychomotor learning. The study lays out a conceptual design framework based on selected learning theories, instructional video design, and digital human representations.